5‐Year clinical follow‐up of the COBRA (complex coronary bifurcation lesions: Randomized comparison of a strategy using a dedicated self‐expanding biolimus A9‐eluting stent vs. a culotte strategy using everolimus‐eluting stents) study. Issue 6 (14th March 2018) - Bennett, J.; Adriaenssens, T.; McCutcheon, K.; Dens, J.; Desmet, W.; Sinnaeve, P.; Vrolix, M.; Dubois, C.
Abstract: Objectives: We evaluated healing responses with optical coherence tomography, and long‐term clinical outcomes after treatment with a dedicated stent versus a conventional culotte technique. Background: Dedicated bifurcation stents have been proposed as an alternative treatment for coronary bifurcation lesions. The long‐term performance of dedicated stents versus conventional dual‐stent techniques for the treatment of complex coronary bifurcation lesions is unknown. Methods: Forty patients with true coronary bifurcation lesions were randomized to treatment with a dedicated Axxess bifurcation stent in the proximal main vessel and additional Biomatrix stents in branches versus culotte stenting using Xience stents. Results: The percentage of uncovered struts in each bifurcation segment at 9 months (primary endpoint) was similar between groups. Five‐year clinical follow‐up was available for all patients and included major adverse cardiac events [MACE; a composite of cardiac death, myocardial infarction (MI) and ischemia‐driven target lesion revascularization (TLR)], target‐vessel (TVR) and non‐target‐vessel revascularization (non‐TVR), non‐TLR and stent thrombosis. At 5 years, in the culotte group, one patient had undergone TLR and another suffered a clinical MI, resulting in 10% MACE versus none in the Axxess group. TVR (5% vs. 10%, P = 0.54) and non‐TVR (5% vs. 20%, P = 0.39) rates were similar between the Axxess and culotte groups, respectively. There was no stent thrombosis. Conclusion: Compared with culotte stenting with Xience, complex coronary bifurcation stenting using a dedicated strategy combining the Axxess and Biomatrix stents results in similar stent strut coverage at 9 months, and excellent clinical outcomes at 5 years.